Web-Based Online Learning Using the CodeIgniter Framework at SMAN 1 Pringgarata - Muhamad Masjun Efendi; Zakaria, Ahmad (International Journal of Science, Technology and Applications, 2023)
Education is very important. SMAN 1 Pringgarata is an educational institution that will produce competent human resources. The development of technology is so rapid, SMAN 1 Pringgarata can take advantage of technological developments by applying online learning methods. The online learning system is the application of learning methods with information technology that can help the teaching and learning process to be more optimal by cooperating with traditional systems with online learning systems. The purpose of this research is to design and implement a website-based learning system in order to provide more varied learning methods for students. The method used in making the online learning system is the waterfall method, this method is a research model that is systematic, sequential in building software. The programming used in building the online learning system is the codeigniter framework and MySQL as the database. Learning with the online system method makes it easier for teachers to be able to distribute subject matter to students and students get learning materials anytime and anywhere with internet media